2020
DOI: 10.1016/j.redox.2020.101653
|View full text |Cite|
|
Sign up to set email alerts
|

Symmetrical dimethylation of H4R3: A bridge linking DNA damage and repair upon oxidative stress

Abstract: The DNA lesions caused by oxidative damage are principally repaired by the base excision repair (BER) pathway. 8-oxoguanine DNA glycosylase 1 (OGG1) initiates BER through recognizing and cleaving the oxidatively damaged nucleobase 8-oxo-7,8-dihydroguanine (8-oxoG). How the BER machinery detects and accesses lesions within the context of chromatin is largely unknown. Here, we found that the symmetrical dimethylarginine of histone H4 (producing H4R3me2s) serves as a bridge between DNA damage and subsequent repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In keeping with the antioxidative function of PRMT5, knockdown of PRMT5 in ovarian cancer cells increased levels of ROS [ 63 ]. Oxidative stress has also been reported to lead to PRMT5-mediated increase in H4R3 symmetric dimethylation and the base excision repair complex assembly that ensured oxidative DNA lesion repair [ 64 ]. However, a study in renal cells subjected to ischemia-reperfusion stress found that inhibition of PRMT5 ameliorated pyroptosis and oxidative stress [ 65 ] and glutathionylation was found to decrease PRMT5 activity [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the antioxidative function of PRMT5, knockdown of PRMT5 in ovarian cancer cells increased levels of ROS [ 63 ]. Oxidative stress has also been reported to lead to PRMT5-mediated increase in H4R3 symmetric dimethylation and the base excision repair complex assembly that ensured oxidative DNA lesion repair [ 64 ]. However, a study in renal cells subjected to ischemia-reperfusion stress found that inhibition of PRMT5 ameliorated pyroptosis and oxidative stress [ 65 ] and glutathionylation was found to decrease PRMT5 activity [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the antioxidative function of PRMT5, knockdown of PRMT5 in ovarian cancer cells increased levels of ROS (57). Oxidative stress has also been reported to lead to PRMT5-mediated increase in H4R3 symmetric dimethylation and the base excision repair complex assembly that ensured oxidative DNA lesion repair (58). However, a study in renal cells subjected to ischemia-reperfusion stress found that inhibition of PRMT5 ameliorated pyrroptosis and oxidative stress (59) and glutathionylation was found to decrease PRMT5 activity (60).…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27). Base excision repair (BER) is the main method to repair DNA damage caused by oxidative stress (28). The function of FEN1 in long-patch base excision repair appears to be particularly important in the repair of damage caused by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%